Design and its characteristic analysis of a wheeled train uncoupling robot with multi-degrees-of-freedom. (June 2016) - Yao, Jianjun; Huang, Yuxuan; Jiang, Guilin; Gao, Shuang; Xiao, Rui; Yu, Han
Freight trains play a vital role in cargo transportation in the world. The freight cars need to be redistributed for marshalling according to different destinations in the hump yard. Humans are usually employed to uncouple the freight cars in the marshalling yard. However, the work environment is difficult to work in, because of its potential danger and the effects of the surrounding environment can have a very serious impact on human's health. A wheeled robot is developed to replace humans to finish the uncoupling task. It has four degrees-of-freedom with flexible motion. Based on the D-H method, the kinematics, including the forward and the inverse kinematics, is firstly analysed. The dynamic analysis is then studied by Newton–Euler equations. The workspace is lastly investigated to verify its operational space such that the coupler can be easily reached by the robot manipulator. Those characteristic analyses provide a basis for motion planning and real-time control of the robot.